2022
DOI: 10.1093/brain/awac328
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted role of neurofilament light chain protein in non-primary neurological diseases

Abstract: The advancing validation and exploitation of cerebrospinal fluid and blood neurofilament light chain protein as a biomarker of neuroaxonal damage has deeply changed the current diagnostic and prognostic approach to neurological diseases. Further, recent studies have provided evidence of potential new applications of this biomarker also in non-primary neurological diseases. In the present review we summarise the current evidence, future perspectives, but also limitations, of neurofilament light chain protein as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 186 publications
3
37
0
Order By: Relevance
“…And, third, the nature of the study design of the sample populations included in the present study derived in an enrichment of individuals with depression, cardiovascular risk factors and cardiovascular disease. While most prior research focused on neurological conditions, recent studies have shown increased levels of sNfL in patients with cardiovascular or metabolic conditions and multimorbidity ( 39 ). In fact, we also showed this to be the case in the BiDirect study.…”
Section: Discussionmentioning
confidence: 99%
“…And, third, the nature of the study design of the sample populations included in the present study derived in an enrichment of individuals with depression, cardiovascular risk factors and cardiovascular disease. While most prior research focused on neurological conditions, recent studies have shown increased levels of sNfL in patients with cardiovascular or metabolic conditions and multimorbidity ( 39 ). In fact, we also showed this to be the case in the BiDirect study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the potential influence on sNfl levels, patients with a previous history of cancer were excluded, excepting thymoma ( 31 ). Other exclusion criteria were diagnosis of polyneuropathy, neurodegenerative diseases (atypical and typical parkinsonian disorders, frontotemporal dementia, Alzheimer's disease, and amyotrophic lateral sclerosis (ALS)), central nervous inflammatory diseases (multiple sclerosis and autoimmune encephalitis), traumatic brain injury, and previous stay on intensive care unit (< 3 months) ( 32 ). Overall, 134 patients could be included for baseline analysis and were followed up to 3 years.…”
Section: Methodsmentioning
confidence: 99%
“…Neurofilament light chain (NfL) is a protein that is found throughout the central and peripheral nervous system in the axons of nerve cells under physiological conditions, and in the blood and CSF in some pathologies involving significant nerve damages [ 36 ]. NfLs are the most abundant and soluble cytosolic subunits of the neurofilaments that give structural stability to the axons, dendrites, and somas [ 37 ].…”
Section: Salivary Biomarkersmentioning
confidence: 99%